From Mandatory To Voluntary: The Impacts on Brazilian Union Funding After The Labor Reform (REMUNOM, 2025)
This article analyzes the impacts of the 2017 labor reform on union funding in Brazil, which made previously mandatory union contributions optional. The objective is to understand how this legislative change affected the financial sustainability of union entities. This is a qualitative study conducted through a bibliographic survey of recent academic publications. The results indicate that the drastic reduction in revenue compromised the operational capacity and representation of unions, requiring the adoption of new funding strategies. Despite recent legal advancements that flexibilize the collection of certain contributions, significant challenges remain for maintaining and strengthening union activities.